Assessment of Residential Accessibility to School Distribution in Oebobo Sub-district, Kupang City - Maria Anjelina Reti; Muhammad Husain Hasan; Andrinata, Andrinata (Tinta Emas Institute, 2024)
Educational inequality in Indonesia is often influenced by socioeconomic differences and the distribution of educational facilities, which is the focus of the implementation of the zoning system in Oebobo sub-district, Kupang city, in accordance with Permendikbud No. 14/2018. This study aims to evaluate the level of accessibility to schools at different levels of education-Kindergarten, primary, junior secondary and senior secondary-and analyze the impact of the zoning system on this accessibility. Using mixed methods, this study combines quantitative data from questionnaires with qualitative data from field surveys to get a comprehensive picture of distance, time, cost, type of transportation and road conditions. The results show that kindergartens have the highest accessibility score (21) and fall into the very adequate category, while primary, junior and senior high schools obtain lower scores but remain in the adequate category (15-18). Road damage such as potholes and grain dislodgement had a significant effect on the accessibility score. Based on these results, it is recommended that the zoning system should still be implemented to ensure equitable distribution of students and reduce the stigma of favorite schools. In addition, it is necessary to map transportation routes, improve road conditions, and update zoning maps to meet the needs and latest developments in Oebobo Sub-district.